Advertising, Perceived Value, Social Influence and Purchase Mangament - Asty Almaida; Romi Setiawan; Sri Kurnia Ramadhani (International Journal of Supply Chain Management, 2019)
This study aims to examine the role of advertising, perceived value, and social influence in purchasing managements on cosmetic products. The data used in this research was obtained from questionnaires. The research model was tested quantitatively through a field survey of 257 Hasanuddin university students using multiple linear regression analysis with SPSS 23 (Statistical Product and Service Solutions). The results of this study indicate that advertising, perceived value and social influence have positive influence on purchase management. Advertising and perceived value are two variable that have significant influence on purchase management. Given the importance of consumer purchasing managements for business sustainability and often contributing strategically, this research has implications for theoretical and practical development.